Towards Industry 4.0: a SWOT-based analysis for companies located in the Sorocaba Metropolitan Region (São Paulo State, Brazil) - Firmino,Alessandro Silveira (2020)
Abstract: The concept of Industry 4.0 was first introduced in Germany in 2011. Also called as the 4th industrial revolution, this concept is based on digitization and integration of physical and digital media, focusing on the automation of production processes and integration across the value chain. Due to the fast development of Industry 4.0 in the last few years, this study performed a SWOT-based analysis to assess strategic points to develop and apply digital technologies in the companies situated at the SMR – Sorocaba Metropolitan Region (São Paulo State, Brazil). A literature review was developed on Industry 4.0 conception and its main technologies: Cyber-Physical Systems, Internet of Things, Intelligent Factories and Big Data. Findings from the literature review were used to develop an exploratory questionnaire (survey), which was applied to SMR’s companies’ representatives. After that, a SWOT matrix was applied, to generate action plans to facilitate the insertion of Industry 4.0 in the companies from the SMR, based on offensive, confrontational, reinforcement and defense strategies selection. The strategies proposed on this paper should be used as an input for public political issues in the SMR, and they could also be expanded to other regions in Brazil as short and long-term strategies.